Functional Interaction between Pleiotropic Transactivator pUL69 of Human Cytomegalovirus and the Human Homolog of Yeast Chromatin Regulatory Protein SPT6 - Winkler, Michael (American Society for Microbiology, 2000)
The phosphoprotein pUL69 of human cytomegalovirus (HCMV), which is a herpesvirus of considerable medical importance in immunosuppressed patients and newborns, has previously been identified as an early-late viral protein that can stimulate several viral and cellular promoters and thus exerts a rather broad activation pattern. To gain insight into the mechanism of this transactivation process, we looked for cellular factors interacting with pUL69 in a yeast two-hybrid screen. Using a B-lymphocyte cDNA library fused to the GAL4 activation domain, we identified 34 clones, 11 of which comprised one distinct gene. Interaction with this gene turned out to be very strong, producing β-galactosidase levels 100-fold greater than the background as measured in an ONPG (o-nitrophenyl-β-d-galactopyranoside) assay. Sequencing identified this gene as the human homolog of the yeast factor SPT6, which is thought to be involved in the regulation of chromatin structure. A direct interaction of pUL69 and the carboxy terminus of hSPT6 could be demonstrated using in vitro pull-down experiments. After having generated a specific antiserum that is able to detect the endogenous hSPT6 protein, we were able to observe an in vivo interaction of both proteins by coimmunoprecipitation analysis. The interaction domain within pUL69 was mapped to a central domain of this viral protein that is conserved within the homologous proteins of other herpesviruses such as the ICP27 protein of herpes simplex virus. Internal deletions within this central domain, as well as a single amino acid exchange at position C495, resulted in a loss of interaction. This correlated with a loss of the transactivation potential of the respective mutants, suggesting that the hSPT6 interaction of pUL69 is essential for stimulating gene expression. Furthermore, we demonstrate that the carboxy terminus of hSPT6 also binds to histon H3 and that this interaction can be antagonized by pUL69. This allows the deduction of a model by which pUL69 acts as an antirepressor by competing for binding of histones to hSPT6, thereby antagonizing the chromatin remodeling function of this cellular protein.